Gambaran Perilaku Pencegahan Kanker Serviks Pada Wanita Pasangan Usia Subur di Puskesmas Rewarangga - Julinda Malehere; Ni Ketut Alit Armini; Elida Ulfiana (Universitas Airlangga, 2019)
Introduction: Cervical cancer is the third cancer cause and the fourth leading cause of death for all types of cancer in women worldwide. Cervical cancer can be prevented and cured by early detection because it has a long preinvasive phase. The purpose of this study was to describe the prevention behavior of cervical cancer in woman couple of reproductive ages in Rewarangga Community Health Center.Methods: This research method was a descriptive study involving 196 respondents, taken by cluster random sampling. Data were collected using a questionnaire about respondent characteristics and prevention behavior of cervical cancer.Results: Most of the respondents aged between 36-45 years were 109 people (55.6%), seen from the education level almost half had elementary school education as many as 92 people (46.9%), in terms of employment almost half of the respondents did not work as many as 91 people (46.4%), and in terms of family income almost all of them have family income below the UMR <Rp 1,000,000 as many as 174 people (88.8%), the majority of respondents had a behavior of prevention of positive cervical cancer by 143 people (72.9%).Conclusion: The results showed a description of the prevention behavior of cervical cancer in women couple of reproductive ages based on demographic data of age, education, occupation, family income in obtaining the majority of positive cervical cancer prevention behaviors in the form of non-smoking behavior, not having free sex, consuming vegetables and fruit and not using KB long pill, but the behavior of cervical cancer screening with IVA method almost all respondents have never done it. It is expected that the efforts of health workers in providing education related to cervical cancer screening using the IVA method as an effort to prevent cervical cancer.